2019
DOI: 10.1186/s13567-019-0656-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the non-glandular gastric region microbiota in Helicobacter suis-infected versus non-infected pigs identifies a potential role for Fusobacterium gastrosuis in gastric ulceration

Abstract: Helicobacter suis has been associated with development of gastric ulcers in the non-glandular part of the porcine stomach, possibly by affecting gastric acid secretion and altering the gastric microbiota. Fusobacterium gastrosuis is highly abundant in the gastric microbiota of H. suis -infected pigs and it was hypothesized that this micro-organism could play a role in the development of gastric ulceration. The aim of this study was to obtain further insi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Among them, Fusobacterium , Helicobacter , and Butycicoccus were identified as marker microorganisms in group S using LEfSe. As we know, Fusobacterium has been associated with gastric ulcers in pigs [ 49 ] and colon carcinoma in humans [ 50 , 51 ], and may represent a kind of new opportunistic pathogens of chickens worthy of further investigation [ 52 ]. In addition, in the species level, Helicobacter_pullorum has also been identified as a marker microorganism of group S, which is member of Campilobacterota and a well-known zoonotic pathogen [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, Fusobacterium , Helicobacter , and Butycicoccus were identified as marker microorganisms in group S using LEfSe. As we know, Fusobacterium has been associated with gastric ulcers in pigs [ 49 ] and colon carcinoma in humans [ 50 , 51 ], and may represent a kind of new opportunistic pathogens of chickens worthy of further investigation [ 52 ]. In addition, in the species level, Helicobacter_pullorum has also been identified as a marker microorganism of group S, which is member of Campilobacterota and a well-known zoonotic pathogen [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Fusobacterium gastrosuis (F. gastrosuis) is identified based on 16S rRNA and gyrase B genes, and it was hypothesized that this micro-organism could play a role in the development of gastric ulceration because most Fusobacterium spp can aggravate necrosis [22]. H. suis-infected pigs showed a significantly higher colonization rate of F. gastrosuis in the non-glandular gastric region compared to non-infected pigs [23]. A previous study has demonstrated an association between gastric lesions and a carbohydrate-enriched liquid diet when mono-infected with Lactobacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the pathogen properties and on wild boar density and management, the eco-epidemiological role of these animals can vary from a dead-end over spill over, up to maintenance host [ 3 , 4 ]. Contacts between wild boars and outdoor domestic pigs should be considered a risk for transmission of these pathogens that can directly affect the swine production and animal welfare, since wild boars and domestic pigs belong to the same species ( Sus scrofa ) [ 3 , 4 , 17 , 19 , 30 ].…”
Section: Resultsmentioning
confidence: 99%